2022
DOI: 10.1029/2021wr031530
|View full text |Cite
|
Sign up to set email alerts
|

Salt Transport Under Tide and Evaporation in a Subtropical Wetland: Field Monitoring and Numerical Simulation

Abstract: Tidal wetlands are connected with coastal estuarine systems and typically have a low-lying intertidal area with a more elevated supratidal zone (Sheaves & Johnston, 2008;Snedden et al., 2012). The low-lying intertidal wetland surface is regularly inundated by saline seawater from tidal creeks and drainage channels within the wetland (Wolanski & Elliott, 2016). This induces complex porewater-seawater mixing in the wetland aquifer. The abundance of salts in the wetland soil creates a brackish-saline environment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The near-surface layer (< 7 m deep) had an averaged resistivity of 1.17 AE 0.08 and 1.31 AE 0.24 ΩÁm for A-A' and B-B 0 , respectively. Relatively lower and more spatially variable salinity in this layer is a combined result of multiple processes including tidal flooding, rainwater infiltration and evaporation at the atmosphere-soil interface (Liu et al 2022). Resistivity gradually increased for the lower layer (35-58 m deep), indicating a salinity transition in the aquitard between the unconfined aquifer and the confined aquifer.…”
Section: Origin and Possible Driving Forces Of Springsmentioning
confidence: 99%
“…The near-surface layer (< 7 m deep) had an averaged resistivity of 1.17 AE 0.08 and 1.31 AE 0.24 ΩÁm for A-A' and B-B 0 , respectively. Relatively lower and more spatially variable salinity in this layer is a combined result of multiple processes including tidal flooding, rainwater infiltration and evaporation at the atmosphere-soil interface (Liu et al 2022). Resistivity gradually increased for the lower layer (35-58 m deep), indicating a salinity transition in the aquitard between the unconfined aquifer and the confined aquifer.…”
Section: Origin and Possible Driving Forces Of Springsmentioning
confidence: 99%
“…Numerous studies have revealed that evaporation from beaches underlain by saline groundwater leads to significant salt accumulation near the surface, thereby altering the magnitudes and pathways of groundwater flow (Liu et al., 2022; Yu et al., 2021). However, quantitative studies of these effects have primarily focused on evaporation from the unsaturated beach surface, where pore‐water pressure is below atmospheric levels (e.g., Geng et al., 2023; Shen et al., 2018; Xin et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In wetland systems with a shallow groundwater table, the near‐surface region usually has a relatively high water content (due to strong capillary forces), which facilitates pore water evaporation from the sediments (Mahfouf & Noilhan, 1991; Xin et al., 2017). The shallow groundwater table also builds a strong hydraulic connection between the evaporation front and deep surrounding groundwater, which efficiently replenishes the loss of water evaporated near the wetland surface, resulting in a sustainable evaporation rate on the surface (Liu et al., 2022). In wetlands, the large‐scale hydraulic gradients induce lateral groundwater flow to the depression areas, while strong evaporation drives pore water to flow upward.…”
Section: Introductionmentioning
confidence: 99%